Integrated continuous care: implementation in Mato Grosso do Sul, Brazil (Bioscience Journal, 2020)
The demographic transition that occurred in Brazil brought changes in its health indicators. Integrated Continuous Care (ICC) was organized as a health care model aimed at increasing the independence and well-being of people with acute or recent functional dependence. This study aimed to describe the development and implementation of the Integrated Continuous Care in the state of Mato Grosso do Sul, Brazil. This care model utilized the principles of the National Humanization Policy, such as the extended and shared clinic, embracement, educational practices and meetings with caregivers, families, and patients, open visits, participation and autonomy of the patient and family in the construction of the Singular Therapeutic Project, and shared discharge from hospital. Assistance and support to patients who were already released from ICC must be increased in the primary health care setting to ensure continuity of recovery, better readaptation, and successful family and social reintegration. As a positive result, we set up an outpatient clinic for ICC patients who needed continuous clinical follow-up after rehabilitation. This allows patient re-evaluation, reduces re-admission rates, and maintains the domiciliary care management educational process. As an innovative approach to improving health care outcomes, ICC allows the patients to leave the hospital environment and go home on some weekends. The ICC project has enabled many advances, especially in patient-centered care and shared decision-making. The support of the São Julião Hospital administration has been vital to the success of ICC Unit treatments.